The Significance of Mitophagy in Myocardial Ischaemia/ Reperfusion: the effect of melatonin - Dube, Kopano Rebaona (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.